2007
DOI: 10.1080/13571510701597353
|View full text |Cite
|
Sign up to set email alerts
|

The Economics of State Subsidies in Early Stage Financing

Abstract: We analyze the effect of state subsidies on early stage investments. In a two‐period investment model with incomplete stage financing contracts, we describe optimal and second‐best investment levels. Optimality depends on external effects: given that private early stage financing generates positive external effects, the subsidies might be designed to use scarce state money most efficiently to mobilize private investment capital. However, a subsidy might also contribute to greater efficiency of the contractual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 46 publications
0
6
0
1
Order By: Relevance
“…We also found two outliers. Bauer -Burghof (2007) investigated the government measures from a theoretical point of view. A merely theoretical basis forms the motivation for the article of Herrera-Echeverri et al (2014) as well, since they want to uncover whether the neoclassical or Keynesian theories on governmental intervention are beneficial for the emerging markets when it comes to the health of the VC industry.…”
Section: Relevance Of the Articlesmentioning
confidence: 99%
See 3 more Smart Citations
“…We also found two outliers. Bauer -Burghof (2007) investigated the government measures from a theoretical point of view. A merely theoretical basis forms the motivation for the article of Herrera-Echeverri et al (2014) as well, since they want to uncover whether the neoclassical or Keynesian theories on governmental intervention are beneficial for the emerging markets when it comes to the health of the VC industry.…”
Section: Relevance Of the Articlesmentioning
confidence: 99%
“…Based on a theoretical analysis, Bauer -Burghof (2007) proved that the state intervention is most effective using scarce state money meanwhile mobilizing private capital, its role is essentially to promote getting PVC investment. Wonglimpiyarat (2016) also found that the GVC investments in Israel did not crowd out, but crowd in private investments.…”
Section: Pure Gvcmentioning
confidence: 99%
See 2 more Smart Citations
“…Cornelli and Yosha (1998), Gompers (1995), Sahlman (1990) pointed out the rights that investors could give up the investment liquidate at any stage are not only the pressures on the management of risk enterprises but also the incentives on the management. Therefore, stage financing is a kind of incentive method to risk enterprises [ 5 , 18 25 ].…”
Section: Related Workmentioning
confidence: 99%